Peningkatan Daya Tarik Candi Muaro Jambi Melalui Promosi Visual dan Fasilitas - Irana, Dasmita; Zarkasih, Mhd Hafidz; Ramadhan, Rico Oktaviano; Pahlefi, Reza; Syamsiah, Syamsiah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Muaro Jambi Temple is one of Southeast Asia's largest cultural heritage sites, renowned for its historical, archaeological, and educational value. This study aims to explore various aspects of Muaro Jambi Temple, including its potential as a tourist destination, a source of historical learning, and its contribution to the local economy. Using a qualitative approach through literature analysis, the study identifies the relationship between cultural preservation, facility management, and the promotion of the temple complex. The findings reveal that Muaro Jambi Temple serves not only as a centre for cultural and religious tourism but also as an innovative educational resource for historical learning. Furthermore, environmental and facility management in the temple area play a crucial role in attracting tourists. However, challenges such as limited public awareness and insufficient promotion hinder the optimization of the site's potential. Therefore, collaboration among the government, academics, and local communities is essential to preserve and develop Muaro Jambi Temple as a sustainable cultural and educational hub.